Isolation and identification of an agar-liquefying marine bacterium and some properties of its extracellular agarases - FATURRAHMAN FATURRAHMAN; ANJA MERYANDINI; MUHAMMAD ZAIRIN JUNIOR; IMAN RUSMANA (Society for Indonesian Biodiversity, 2011)
Faturrahman, Meryandini A, Junior MZ, Rusmana I (2011) Isolation and identification of an agar-liquefying marine bacterium and some properties of its extracellular agarases. Biodiversitas 12: 192-197. A new agar-liquefying bacterium, designated Alg3.1, was isolated from Gracilaria samples collected from the Kuta Coast at Central Lombok in West Nusa Tenggara and was identified as Aeromonas sp. on the basis of morphology, biochemical-physiological character and 16S rDNA gene sequencing. The bacterium appeared capable of liquefying agar in nutrient agar-plate within 48 hours of incubation and the agar was completely liquefied after l5 days at 29oC. When the isolate was grown in basal salts solution medium B supplemented with peptone and yeast extract, producedextracellular agarases within a short period of time (4-16 h) and the maximum agarase activity was 0.489 nkat/mL at 36h after incubation.